From One Woman to Another: The Role of Spanish Women in the Catholic Education of Indigenous Girls in Sixteenth Century New Spain - Green, Kayla E (East Carolina University, 2018)
The endeavors of the colonial enterprise of the Spanish empire are often attributed to men while women are given secondary importance; yet women were greatly involved in the religious education and conversion of indigenous girls. Religious laywomen, or beatas, served as religious teachers to indigenous daughters of nobility, helping to shape colonial society. The beatas garnered great support of their work from Spain's Queen Isabella of Portugal. Through Isabella's writings in the 1530s, her support for the spread of Catholicism and her respect for the women carrying out God's instructions to convert the world is evident. Isabella favored the "soft imperialistic" tactics of the beatas as opposed to many of the male priests' employment of violent and fear tactics of conversion. The beatas struggled, however, to assert their autonomy in colonial society as the patriarchy attempted to control them and their work. From one woman to another, Queen Isabella of Portugal and the beatas of New Spain worked together to advocate for the Spanish women's rights as educators, for the indigenous girls of noble status, and for their education. Through the beatas' fight for their independence, they attempted to revolutionize imperial modes of conquest and control and, thus, colonial society. Queen Isabella of Portugal and the beatas of New Spain are without a doubt significant actors in history, serving as purveyors of change, advocates of religious conversion and education, and supporters of women's autonomy, and as such, their story deserves an audience.
Keywords: Mexico; colonialism; Spanish women; Nahua; imperialism; Queen Isabella of Portugal; gender; beatas; education; power; Catholic women--Religious life--History--16th century; New Spain--Church history--16th century; Catholic Church--Spain--History--16th century; Colonization--Religious aspects--History--16th century; Indigenous women--Cultural assimilation; Conversion